(3MRH GdfhQ hJeGe GdSQhQs - (3CMeO Hf eMeO Hf YHO GdcQje Hf YWGA Gddg GdScfOQj, GHf YWGA Gddg , JGL GdOjf CHh GdaVd,J (B709 (3g` s
(3ChdgG (B:s
(3hHYO agPG MRH GdfhQ hJeGe GdSQhQ hef bQCg hMedg cGf eMahXkG ef LejY GdeNGha egGHkG ebHhdkG hjbVi Gddg dg LejY MhGFLg s
(3BNQgG (B:s
(3SHMGf GdPj SNQ dfG gP heG cfG dg ebQfjf hEfG Edi QHfG defbdHhf hGdMeO ddg QH GdYGdejf Je gPG GdMRH GdfhQ hJeGe GdSQhQ s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B221 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B121s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs